Hello My Melo Friend!
Formula: [tex]y = a(x-h)^2 + k[/tex]
[tex]f (x) = a(x-4)^2 - 1[/tex]
[tex]15 = a(0-4)^2 - 1[/tex]
[tex]15 = a(-4)^2 - 1[/tex]
[tex]15 = a(16) - 1[/tex]
[tex]15 +1 = 16a[/tex]
[tex]16 = 16a[/tex]
[tex]16/16 = 16a/16[/tex]
[tex]1 = a[/tex]
A MUST be = to 1
[tex]y = (x-4)^2 - 1[/tex]
[tex]y = x^2 - 8x + 16 - 1[/tex]
[tex]y = x^2 - 8x + 15[/tex]
Factor = (Find two number that summed give [tex]-8 [/tex]and multiplied [tex]+15[/tex])
[tex](x-3)(x-5) = 0[/tex]
[tex](x-3) = 0 -\ \textgreater \ x = 3[/tex]
[tex](x-5) = 0 -\ \textgreater \ x = 5[/tex]
Therefore, The Correct Answer would = to [tex](3;0)[/tex] and [tex](5;0)[/tex].
I Hope my answer has come to your Help. Thank you for posting your question here in [tex]Brainly. [/tex]We hope to answer more of your questions and inquiries soon. Have a nice day ahead! :)
[tex](Ps. Mark As Brainliest IF Helped!)[/tex]
[tex]-TheOneAboveAll :D[/tex]